Osteoarthritis management care pathways are complex and inefficient: A qualitative study of physiotherapist perspectives from specialised osteoarthritis services. (11th April 2022) - Gibbs, Alison J.; Wallis, Jason A.; Taylor, Nicholas F.; Kemp, Joanne L.; Barton, Christian J.
Abstract: Objective: Hip and knee osteoarthritis guidelines internationally provide consistent first‐line care recommendations. However, uptake of these recommendations remains suboptimal. This qualitative study explores factors influencing guideline‐based care from the perspectives of physiotherapists working in specialised osteoarthritis services across different models of care. Methods: Nineteen semi‐structured interviews were conducted with physiotherapists working in specialist osteoarthritis services across three different Australian models of care (OsteoArthritis Hip and Knee Service n = 10; OsteoArthritis Chronic Care Programme n = 4; Orthopaedic Physiotherapy Screening Clinics and Multidisciplinary Services n = 5). Interviews were audio recorded and transcribed verbatim. Data were coded and analysed inductively using thematic analysis. Results: The overarching theme to emerge was that accessing first‐line osteoarthritis care is complex and difficult, regardless of model of care. Subthemes indicated that: (i) services are either unavailable or inadequately funded, (ii) referral pathways are labyrinthine and lengthy, (iii) patients and other health professionals often believe that surgery is the only/best option and (iv) managing patient co‐morbidities is challenging. Conclusion: Physiotherapists working in specialised osteoarthritis services perceive multiple and complex factors influencing adherence to first‐line care. Barriers occur at various levels in all models of care, including patient and health professional beliefs, health service, and system levels. These results suggest improving healthcare for people with osteoarthritis requires urgent system reform.